Causal Interaction among Electricity Consumption, Financial Development, Exports and Economic Growth in Jordan: Dynamic Simultaneous Equation Models - Matar, Ali; Bekhet, Hussain Ali (International Journal of Energy Economics and Policy, 2015)
The goal of this paper is to examine the empirical dynamic relationship among the electrical consumption and economic growth (proxies by GDP per capita), export, and financial development (domestic credit to the private sector as a percentage of GDP) in Jordan over the 1976-2011 period. Annual time series data and the Autoregressive distributed lag (ARDL) model are used. The ADF, F-bound testing, Granger causality, GIRF, and CUSUM, CUSUMQ tests were applied to test the stationary, co-integration, causality and stability, respectively, among the variables. There is evidence of a long-term equilibrium relationship between electricity consumption and the economic growth, and a unidirectional relationship runs from real GDP to electrical consumption (ELC). This is indicating that per capita increase in economic growth may cause a perpetual rise in the ELC in Jordan. Keywords: Electricity Consumption; Economic Growth; Co-integration; ARDL; Causality; Jordan. JEL Classifications: C32; O13; O20; Q43